Pengaruh Pelatihan Kerja dan Motivasi Kerja Terhadap Produktivitas Kerja Karyawan yang Berimplikasi Pada Kinerja Karyawan (Studi Kasus Pada PT. Inspira AdhiMitra) - Cicih Ratnasih; Aeni Diniawati (Fakultas Ekonomi Universitas Borobudur, 2020)
This study aims to determine the effect of Job Training and Work Motivation on WorkProductivity, either directly or indirectly through Kinerka Employees at PT. Inspira AdhiMitra.The data used in this study are primary data collected through questionnaires and otherliterature studies. The population in this study were all employees of PT. Indomarco Adi Prima -Main Warehouse Jakarta, Jababeka with a sample size of 70 respondents. The data analysistechnique used path analysis with the help of the SPSS 22 analysis system.The results showed that job training has a significant positive effect on work productivity,motivation has a significant positive effect on work productivity, job training has a significantpositive effect on employee performance, motivation has a significant positive effect on employeeperformance, work productivity has a significant positive effect on employee performance,Keywords: job training, work motivation and employee performance